2021
DOI: 10.1016/j.ijscr.2021.105728
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic repair of diaphragmatic hernia after radiofrequency ablation for hepatocellular carcinoma: Case report

Abstract: Highlights Diaphragmatic hernia is a rare late-onset complication associated with RFA for HCC. The tumor location is closely related to the risk of diaphragmatic hernia caused by RFA. Patients with HCC often have severe liver dysfunction and cirrhosis. Laparoscopic approach is safe and minimally invasive for severe cirrhosis patient. The hernia gate was closed by suture, and vulnerable area was reinforced using mesh.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Recently, laparoscopic surgery for treating DH after RFA was reported [3]. However, our review of the literature in PubMed, using "diaphragmatic hernia" and "radiofrequency ablation" as keywords, revealed that the laparoscopic approach was used in only three cases [2,3,12], and there was no report of the use of the laparoscopic approach for emergency treatment of a similar case of strangulated DH occurring after RFA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, laparoscopic surgery for treating DH after RFA was reported [3]. However, our review of the literature in PubMed, using "diaphragmatic hernia" and "radiofrequency ablation" as keywords, revealed that the laparoscopic approach was used in only three cases [2,3,12], and there was no report of the use of the laparoscopic approach for emergency treatment of a similar case of strangulated DH occurring after RFA.…”
Section: Discussionmentioning
confidence: 99%
“…Accurate diagnosis of DH is difficult owing to its nonspecific symptoms and is occasionally delayed [1]. Unlike laparoscopic surgery, open surgery is a widely accepted surgical approach for DH [2]. However, a recent report showed that the laparoscopic approach has both diagnostic and therapeutic abilities [3]; moreover, laparoscopic surgery is less invasive than open surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Twenty cases of diaphragmatic hernia due to RFA have been reported in English including our case. The background of the patients and the details of RFA are given in Table 1 [ 8 - 21 ]. The details of diaphragmatic hernia and the treatment are presented in Table 2 .…”
Section: Discussionmentioning
confidence: 99%
“…The incidence was less than 0.1% without the application of artificial effusion [10]. Only 13 cases of RFA related DH were reported in English literature (Table 1) [11][12][13][14][15]. All 13 DHs were late-onset, ranging from 7 to 96 months after RFA.…”
Section: Discussionmentioning
confidence: 99%